Risks and treatment for recurrent intraepithelial cervical lesions - A. O. Shumeykina; S. E. Krasilnikov; A. G. Kedrova; A. S. Mansurova; A. L. Chernyshova; I. V. Kachesov; E. B. Logashenko (Опухоли женской репродуктивной системы, 2022)
Background. Persistently high incidence of cervical cancer in Russia and significant number of cases detected in the late stages necessitate the improvement of secondary prophylaxis of this disorder.Aim. To assess risk factors for recurrent high-grade cervical intraepithelial neoplasia (CIN2+) (high grade squamous intraepithelial lesions, HSIL) after cervical conization.Materials and methods. This study included 62 patients with recurrent HSIL treated in Novosibirsk Regional Clinical Oncology Dispensary, E. N. Meshalkin National Medical Research Center, “Zdorovye” LLC, “Avismed” LLC, Tomsk National Research Medical Center of the Russian Academy of Sciences, and Federal Research and Clinical Center for Specialized Medical Care and Medical Technologies, Federal Biomedical Agency of the Russian Federation in 2017–2021. We analyzed patients’ human papillomavirus (HPV) status, performed repeated examination of excised tissue specimens to evaluate the severity of lesions and resection margins, as well as immunohistochemical examinations. We found that mean time to cytologically confirmed recurrent HSIL was 16.0 ± 5.6 months. All patients were HPV-positive. Repeated histological examination demonstrated that 18 samples had positive resection margins or endocervical crypt involv ement. Fifty-seven samples had positive staining for p16 at immunohistochemical examination; 46 samples had  Ki-67 >30 %, which indicated high risk of recurrence. Treatment of patients with recurrent HSIL included repeated excision up to healthy cervical tissues, followed by intravaginal therapy with Cervicon-DIM 100 mg twice a day (for 3 months). Follow-up examinations after 18.0 ± 6.2 months on average showed no HPV persistence and no HSIL recurrence.Conclusion. Endocervical crypt involvement along the primary resection margin, underestimated severity and depth of lesions (at the first surgery), and persistence of HPV infection are the main risk factors for recurrent cervical dysplasia or carcinoma in situ. Combination treatment that includes additional excision with a subsequent course of Cervicon-DIM is sufficient and effective.